If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + (-14) = 0 t + -14 = 0 Reorder the terms: -14 + t = 0 Solving -14 + t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + t = 0 + 14 Combine like terms: -14 + 14 = 0 0 + t = 0 + 14 t = 0 + 14 Combine like terms: 0 + 14 = 14 t = 14 Simplifying t = 14
| 7-4*x=13 | | -4y+7=-21 | | 3b-4=5b-2 | | 9-5n=30 | | 4(b-2)=2(b-6) | | 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 | | 6y-2=14y+62 | | 7x+9=-29 | | 9=x-3 | | 6y-2=14y+64 | | 3h+1=3(h+1) | | 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 | | -6x-1=-1 | | 3(x-5)=6(x-6) | | 14x+23=-93 | | 7x+3(4x-1)=49 | | 12-8x-6=-13x+21 | | -3x-10=-10 | | 2x-4+x=8 | | (4x-7)-(2x-2)= | | -7x+5=-58 | | 64=8r+2 | | 7h=9.1 | | (2x+5x)=20 | | 6n-10=4n-2 | | 7x+2=4x+15 |